Dose optimization and endorectal balloon for internal pudendal arteries sparing in prostate SBRT. (May 2019) - Jaccard, Maud; Lamanna, Giorgio; Dubouloz, Angèle; Rouzaud, Michel; Miralbell, Raymond; Zilli, Thomas
Highlights: Endorectal balloon helps better sparing of internal pudendal arteries. Optimization on internal pudendal arteries strongly reduces the dose to this organ. Internal pudendal arteries can be spared without compromising PTV homogeneity or organs at risk constraints. Abstract: Purpose: Vessel-sparing radiotherapy has shown promising results in preserving erectile function (EF). Using an endorectal balloon (ERB) may help to reduce the dose to the internal pudendal arteries (IPA) by pushing the prostate forward. We tested this hypothesis and evaluated the limits of IPA dose optimization in prostate cancer patients simulated with and without ERB. Materials and methods: Twelve patients with localized disease were simulated both with and without ERB. IPA were delineated on every CT after MRI registration. Planning target volumes (PTV) were planned to receive 36.25 Gy in 5 fractions with a VMAT technique. Twenty-four initial plans were generated using a knowledge-based planning software without any specific constraints for IPA. Additional stepwise optimization was performed until stabilization of the IPA dose or trespassing of PTV homogeneity limits. Results: Without optimization, the median mean IPA dose (Dmean ) was lower with ERB than without (10.5 vs. 12.8 Gy, p  = 0.023). After optimization, the IPA Dmean dropped significantly (from 11.1 to 4.8 Gy) without impairing the PTV dose homogeneity and the organs at risk dose constraints. The comparison of the best-optimized plans with and without ERB showed an optimal sparing of IPA using ERB (28% mean dose reduction, p  = 0.006; median Dmean of 4.1 Gy vs. 5.7 Gy with and without ERB, respectively). Conclusion: IPA dose sparing is feasible without compromising dose prescription and constraints. ERB significantly reduced the dose on IPA compared to plans generated without ERB. As no specific constraints are available for vessel-sparing SBRT, optimal IPA dose reduction should be recommended to maximize EF preservation.